UJI KUALITATIF ANALISIS KANDUNGAN METAMFETAMIN DARI RAMBUT PENGGUNA SABU-SABU MENGGUNAKAN METODE KOLOM EKSTRAKSI - Nur Asyiah Dalimunthe (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Methamphetamine is a stimulant, with a stronger stimulant effect than cocaine or other natural stimulants. Use in large quantities can cause "violence", hallucinations, and psychosis. Generally, methamphetamine is produced as powder-like crystals, large lumps of crystals, or in tablet form. Its use can be smoked through the nose, drunk, smoked like a cigarette, or injected. Shabu-shabu is a strong central nervous system stimulant drug that has an addictive effect when consumed and is a case of drug abuse mostly dominated by methamphetamine so accurate analysis is needed to detect these compounds. Research has been carried out on the initial study of methamphetamine analysis in the hair of shabu-shabu users using the sonication method and the extraction column. Sampling was carried out randomly from the hair of shabu-shabu users as many as 5 (five) hair samples. The prepared hair sample was then sonicated for 45 (forty five) minutes with various solvent system ratios, namely methanol:acetone:ammonia, ethylacetate:methanol:ammonia and chloroform:methanol:acetic acid. The sonicated filtrate was extracted liquid-liquid with methanol. The extract obtained was then analyzed qualitatively using Marquist's reagent which produces a very clear brownish orange color in the methanol:acetone:ammonia solvent system. The results of the sonication filtrate were continued with solid phase extraction using diatomaceous earth adsorbent and analyzed qualitatively with marquish reagent giving a brownish yellow color.